Ferroelectric and ferromagnetic properties of SrTi0.9Fe0.1O3−δ thin films. (January 2015) - Wang, Y.G.; Tang, X.G.; Liu, Q.X.; Jiang, Y.P.; Feng, Z.Y.
Abstract: The SrTi0.9 Fe0.1 O3 −δ thin film grown on the LaNiO3 coated Si(100) substrates was prepared by a sol–gel process. The structure, micrograph, chemical states, electrical and magnetic properties of the thin film were investigated by using X-ray diffractometor (XRD), atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), ferroelectric test system and vibrating sample magnetometer (VSM), respectively. The results showed that the ferroelectric properties with the saturated polarization (2 P s ), remanent polarization (2 P r ) and coercive field (2 E c ) of 12.3 μC/cm 2, 1.58 μC/cm 2 and 33 kV/cm, respectively, at applied field of 200 kV/cm. The average remnant magnetization ( M r ) and saturated magnetization ( M s ) of the thin film were 3.74×10 −2 and 9.22×10 −2  emu/cm 3, respectively. Both the ferroelectric and ferromagnetic properties could be explained by the defect induced and the Fe ion substitution. Such multiferroic thin film was appropriate to be used in the field of multiferroic devices. Highlights: Sr(Ti0.9 Fe0.1 )O3− δ thin film was grown on the LaNiO3 coated Si(100) substrates by a sol–gel process. The leakage current density of the Au/Sr(Ti0.9 Fe0.1 )O3− δ / LaNiO3 film capacitor was reported. The ferroelectric property of the thin film was improved by Fe-doping. The ferromagnetic characteristic of the thin film was clearly observed. The multiferroic behavior could be explained by the defect induced by the Fe ion substitution.